Gerakan Salafi Radikal dalam Konteks Islam Indonesia: Tinjauan Sejarah - Qodir, Zuly (ISLAMICA: Jurnal Studi Keislaman, 2008)
This paper is aimed at describing the advent and development of the radical Salafi movement in Indonesia. Historically speaking, such movement was originated in the Middle East especially in Saudi Arabia, Jordan and Syria. In these countries movements like Hizbut Tahrir and Wahhabiya âto mention but few- were found and well-established. Movements such as these were actually banned subsequently in their countries of origin mainly for propagating the idea of Khilafah and for trying to topple the legitimate government. In Indonesia interestingly, the Salafi radical movements survived and even flourished amid the heavy criticism from their antagonists. Leading campuses in the country such as Bogor Institute for Agriculture (Institut Teknologi Bogor/IPB) became their safe-heavens, as it were. Leaders and followers of Hizbut Tahrir Indonesia (HTI) as well as Islamic Justice Welfare Party (PKS) were graduates of this campus. Hence, it was on this campus that the seed of these Salafi movements was planted. The HTI and PKS must be considered the most important Salafi movements in modern Indonesia. They have played their important role in forming the history of this country. Views have been expressed concerning their nature and agendas. Some maintain that these movements are radical and fundamentalists and bear the political agenda to transform Indonesia into becoming the âIslamic Stateâ. Others are of belief that these movements are moderate and progressive, or else revivalist and neo-fundamentalists. It is on this heated debate that this paper is interested in. It will explore the nature and agendas of these two Salafi movements by referring âfirst- to the views expressed by the experts, and âsecond- the views of the leadership of the Nahdhatul âUlama (NU) and Muhammadiyah, two largest Muslim organization in Indonesia.